Worried sick : how stress hurts us and how to bounce back - Carr, Deborah (Deborah S.) (Pinpoints (Series), 2014)
This book answers many questions about how stress makes us sick and why people cope with stress differently. Deborah Carr provides readers with key themes and contemporary research on the concept of stress. In addition to examining individuals' own sources of strength and vulnerability as an important step toward developing personal strategies to minimize stress and its unhealthy consequences, Carr looks at stressors that we face in everyday life which are symptoms of much larger, sweeping problems in contemporary society. Included are several stress and coping checklists, allowing readers to gauge their own stress levels.